GAMBARAN LIKUIDITAS PROFITABILITAS DAN HARGA SAHAM PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI - Tricia, Youpick Endan; Surachim, Ahim; Tarmedi, Eded (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Objectives - analyze the description of liquidity, profitability and stock prices in automotive companies. Design / methodology / approach - This research method uses descriptive method. Objects in this study are automotive companies listed on the Indonesia Stock Exchange period 2010-2016. Data collection techniques with panel data. Data analysis technique using panel regression analysis technique with the help of Eviews 9. Findings - The results show that: (1) Profitability measured using Return On Equity automotive companies tend to decrease. (2) Liquidity measured using Current Ratio of automotive companies tends to decrease. (3) Automotive company stock price decreasedOriginality / value - This research provides a basis for understanding issues of liquidity, profitability and stock price. The difference of this research with previous research is on object, variable, theory, technique of data analysis and also reference which used by researcher with previous researcher.